THE EFFECT OF PRINCIPAL'S TRANSFORMATIONAL LEADERSHIP STYLE AND WORK MOTIVATION ON THE PERFORMANCE OF STATE HIGH SCHOOL TEACHERS IN KEEROM DISTRICT, PAPUA - Nursima Sigalingging; Eva Solita Pasaribu; Santi Rizki; Ernita Siagian; Marupa Siregar (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of the principal's transformational leadership style and work motivation on the performance of public high school teachers in Keerom Regency, Papua. The background of this study is based on the phenomenon of suboptimal teacher performance characterized by low consistency in the preparation of learning tools, minimal learning innovation, and decreased work motivation due to limited facilities and geographical conditions of the border area. In addition, the principal's leadership practices, which are still administrative, are considered not to fully implement the principles of inspirational and empowering transformational leadership. This study uses a quantitative approach with descriptive and inferential methods. The study population was 92 public high school teachers in Keerom Regency, with a sample of 92 respondents. Data were collected through questionnaires compiled based on indicators of transformational leadership style, work motivation, and teacher performance. The data analysis technique used multiple linear regression to test the partial and simultaneous effects between variables. The results showed that the principal's transformational leadership style had a positive and significant effect on teacher performance. This is evidenced by the t-test showing that the calculated t value of 4.555 is greater than the t- table of 1.987 with a significance level of 0.000 <0.05. Likewise, work motivation has a positive and significant effect on teacher performance with the t-test results showing a calculated t value of 6.683 greater than the t- table of 1.987 with a significance value of 0.000 <0.05. Work motivation has a more dominant influence than transformational leadership style based on the standard beta value of 0.535. Then the principal's transformational leadership style and work motivation simultaneously have a positive and significant effect on teacher performance with the F-test results showing a calculated F value of 92.006 with a significance level of 0.000 <0.05. The coefficient of determination (R²) value of 0.821 indicates that 82.1% of teacher performance variations can be explained by the two variables together, while 17.9% is influenced by other factors outside the variables of this study. This study provides empirical contributions and becomes the basis for recommendations for school principals and the Education Office to improve the quality of teacher performance.